Patient‐reported outcomes in heart failure with preserved vs. reduced ejection fraction: focus on physical independence. (30th August 2020) - Huang, Weiting; Teng, Tiew‐Hwa Katherine; Tay, Wan Ting; Richards, Arthur Mark; Kadam, Umesh; Lawson, Claire A.; Shimizu, Wataru; Loh, Seet Yoong; Anand, Inder; Lam, Carolyn Su Ping
Abstract: Aims: The Kansas City Cardiomyopathy Questionnaire (KCCQ) is a widely used patient‐reported outcome measure in heart failure (HF). The KCCQ was validated in patients with HF with reduced ejection fraction (HFrEF), leaving knowledge gaps regarding its applicability in HF with preserved ejection fraction (HFpEF). This study addresses the psychometric properties of internal consistency and reliability, construct, and known‐group validity of KCCQ in both HFrEF and HFpEF. We aimed to evaluate the psychometric properties of the KCCQ and their prognostic significance in HFpEF and HFrEF, within a large prospective multinational HF cohort. Methods and results: We examined the 23‐item KCCQ in the prospective multinational ASIAN‐HF study [4470 HFrEF (ejection fraction <40%); 921 HFpEF (ejection fraction ≥50%)]. Internal consistency (using Cronbach's alpha) showed high reliability in HFrEF and HFpeF: functional status score: 0.89 and 0.91 and clinical summary score: 0.89 and 0.90, respectively. Confirmatory factor analysis in HFrEF validated the five original domains of KCCQ (physical function, symptoms, self‐efficacy, social limitation, and quality of life); in HFpEF, questions measuring physical function and social limitation had strong correlation ( r = 0.66) and different domains emerged. We proposed an additional physical independence summary score, especially in HFpEF (comprising the original physical function and social limitation domains), which showed good internal consistency ( α = 0.89) and has comparable receiver operating characteristic curve 0.766 ± 0.037 with the clinical summary score (receiver operating characteristic curve 0.774 ± 0.037), in predicting 1 year death and/or HF hospitalization. Conclusions: Our results confirmed the robustness of the KCCQ clinical summary score in HF regardless of ejection fraction group. In the assessment of physical capacity in HFpEF, our results suggest strong interaction with social limitation, and we propose a summary score comprising both components be used.